Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.4048/jbc.2021.24.e16
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Breast Cancer in South Korean Patients with Germline TP53 Gene Mutations

Abstract: Purpose Li-Fraumeni syndrome (LFS) is a rare autosomal cancer syndrome caused by a germline mutation in the TP53 gene. Breast cancer in LFS patients is of various subtypes; however, limited data are available on the clinicopathological features of these subtypes and their appropriate treatments. This study aimed to review the clinical features and treatments for breast cancer in South Korean patients with germline TP53 mutations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Breast cancer showed early onset with a median age of 32-34 years, and in immunohistochemistry staining, the proportion of receptor expression was similar with 84%-90.5% ER positivity, 39.5%-63% HER2 positivity, and 32.8%-53% ER and HER2 co-expression. However, a Korean study by Alyami et al [ 10 ] showed differences in histological features and treatment outcomes. This study reported a lower rate of ER expression and a higher rate of triple-negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Breast cancer showed early onset with a median age of 32-34 years, and in immunohistochemistry staining, the proportion of receptor expression was similar with 84%-90.5% ER positivity, 39.5%-63% HER2 positivity, and 32.8%-53% ER and HER2 co-expression. However, a Korean study by Alyami et al [ 10 ] showed differences in histological features and treatment outcomes. This study reported a lower rate of ER expression and a higher rate of triple-negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [9] investigated the mutations and tumor spectra of LFS in Korean patients and identified two novel frameshift mutations in codons 98 and 27. Other studies on Korean patients have reported other types of mutation, such as frameshift or silent mutation (S2 Table) [9][10][11][12][13][14][15][16][17][18]. Based on the IARC database, the most common hotspot mutations were found in codons 175, 245, 248, 273, and 282 (http://p53.iarc.fr/).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 Another retrospective study evaluated 21 breast cancer patients with LFS from South Korea and reported that around 50% of patients were HER2 positive, and 42% were ER or PR positive. 15 Considering around 20% of all breast cancers are HER2-positive, LFS breast cancer seems to be associated with HER2-positivity. Breast cancers in LFS also tend to have high tumor grade and similar morphologic features to somatic TP53 mutated breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that TP53 variant carriers exhibits a very high risk of contralateral breast cancer [23]. On the other hand, several studies with a limited sample size reported an increased risk of ipsilateral breast tumor recurrence in TP53 variant carriers who had a LFS or LFL syndrome [24][25][26]. Therefore, the risk of ipsilateral breast tumor recurrence and contralateral breast cancer should be taken into consideration when TP53 variant carriers received a surgical therapy.…”
Section: Introductionmentioning
confidence: 99%